The role of epistemological beliefs in STEM faculty's decisions to use culturally relevant pedagogy at Hispanic-Serving Institutions - Mollee Shultz; Jayson Nissen; Eleanor Close; Ben Van Dusen (SpringerOpen, 2022)
Abstract Background The growing understanding of the oppressive inequities that exist in postsecondary education has led to an increasing need for culturally relevant pedagogy. Researchers have found evidence that beliefs about the nature of knowledge predict pedagogical practices. Culturally relevant pedagogy supports students in ways that leverage students' own cultures through three tenets: academic success, cultural competence, and sociopolitical consciousness. If STEM practitioners believe that their disciplines are culture-free, they may not enact culturally relevant pedagogy in their courses. We investigated how and in what forms 40 faculty from mathematics, physics, chemistry, and biology departments at Hispanic-Serving Institutions enacted culturally relevant pedagogy. We used the framework of practical rationality to understand how epistemological beliefs about the nature of their discipline combined with their institutional context impacted instructors' decision to enact practices aligning with the three tenets of culturally relevant pedagogy. Results In total, 35 instructors reported using practices that aligned with the academic success tenet, nine instructors with the cultural competence tenet, and one instructor with the sociopolitical consciousness tenet. Instructors expressed and even lauded their disciplines' separation from culture while simultaneously expressing instructional decisions that aligned with culturally relevant pedagogy. Though never asked directly, six instructors made statements reflecting a "culture-free" belief about knowledge in their discipline such as "To me, mathematics has no color." Five of those instructors also described altering their teaching in ways that aligned with the academic success tenet. The framework of practical rationality helped explain how the instructors' individual obligation (to the needs of individual students) and interpersonal obligation (to the social environment of the classroom) played a role in those decisions. Conclusions Instructors' ability to express two contradictory views may indicate that professional development does not have to change an instructor's epistemological beliefs about their discipline to convince them of the value of enacting culturally relevant pedagogy. We propose departmental changes that could enable instructors to decide to cultivate students' cultural competence and sociopolitical consciousness. Our findings highlight the need for future research investigating the impacts of culturally relevant pedagogical content knowledge on students' experiences.